(untitled) - Bielefeldt, Heiner (Cambridge, U.K., 2003)
Symbolic representation fulfills a crucial function in Kant's practical philosophy because it serves to mediate between the unconditionality of the categorical imperative and the inescapable finiteness of the human being. Heiner Bielefeldt offers a unique perspective on how various facets of Kant's philosophy cohere in this study. He demonstrates how the nature of symbolic representation plays out across all areas of practical philosophy--moral philosophy, legal philosophy, philosophy of history and philosophy of religion.